A new member of the Stictochironomus caffrarius group from West Bengal, India, with emendation of generic diagnosis (Diptera, Chironomidae) - Konar, Sanghamitra (Zootaxa, 2021)
Stictochironomus bengalensis n. sp. is described based on the male adult, pupa and larva from West Bengal, India. The species is a new member of the S. caffrarius group. Generic diagnoses for the pupa and larva are emended to accommodate the characteristics of the species group. In addition, a key to the known males of Stictochironomus from the Oriental region is provided.